Mechanical properties of dissimilar metal joints composed of DP 980 steel and AA 7075-T6. (18th March 2015) - Squires, L.; Lim, Y.C.; Miles, M. P.; Feng, Z.
Abstract : A solid state joining process, called friction bit joining, was used to spot weld aluminium alloy 7075-T6 to dual phase 980 steel. Lap shear failure loads for specimens without adhesive averaged ∼10 kN, while cross-tension specimens averaged 2·8 kN. Addition of adhesive with a thickness up to 500 μm provided a gain of ∼50% to lap shear failure loads, while a much thinner layer of adhesive increased cross-tension failure loads by 20%. Microstructures of the welds were martensitic, but the hardness of the joining bit portion was greater than that of the DP 980, owing to its higher alloy content. Softening in the heat affected zone of a welded joint appeared to be relatively small, though it was enough to cause nugget pullout failures in some lap shear tension specimens. Other failures in lap shear tension were interfacial, while all of the failures in cross-tension were interfacial.